The Implementation of Data Mining to Get The Pattern for Selecting Students' Thesis Title - Vobey Alex Sander; Liza Yulianti; Yupianti Yupianti (Jurnal Komputer, Informasi dan Teknologi, 2021)
Management Study Program is one of the study programs at the Faculty of Economics, The University of Dehasen Bengkulu. Every academic year, students who have fulfilled the credits or are in semester 6 or 7, submit a file for submission of titles to the staff of the study program, then the Head of Study Program will check related to the title submitted, if possible and in accordance with the disside of science, the title is issued will approved and the study program will appoint supervisor 1 and supervisor 2 from the student concerned. The application of the pattern for selecting students’ thesis titles at the Management Study Program, Faculty of Economics, The University of Dehasen Bengkulu was made using the Visual Basic .Net programming language and SQL Server 2008r2 database. In the application, the Levenstein Distance Algorithm has been applied to the new title submission form, where a comparison will be made against previously accepted titles that have been stored in the database. The title is accepted if the similarity level is below 50%, while the title is Rejected if the similarity level is above 50%. Based on the trial for submitting a new title, the application is able to provide information on whether the title is accepted or Rejected based on the Levenstein Distance Algorithm approach. Based on the results of the tests that have been carried out, the functionalities of the application run as expected and the application is able to display the results of the analysis through the stages of the Levenstein Distance Algorithm for the submission of new titles.